Characterization of Third Generation Cephalosporin- and Carbapenem-Resistant Aeromonas Isolates from Municipal and Hospital Wastewater - Sara Drk; Ana Puljko; Mia Dželalija; Nikolina Udiković-Kolić (MDPI AG, 2023)
Antibiotic resistance (AR) remains one of the greatest threats to global health, and Aeromonas species have the potential to spread AR in the aquatic environment. The spread of resistance to antibiotics important to human health, such as third-generation cephalosporins (3GCs) and carbapenems, is of great concern. We isolated and identified 15 cefotaxime (3GC)- and 51 carbapenem-resistant Aeromonas spp. from untreated hospital and treated municipal wastewater in January 2020. The most common species were Aeromonas caviae (58%), A. hydrophila (17%), A. media (11%), and A. veronii (11%). Almost all isolates exhibited a multidrug-resistant phenotype and harboured a diverse plasmidome, with the plasmid replicons ColE, IncU, and IncR being the most frequently detected. The most prevalent carbapenemase gene was the plasmid-associated blaKPC-2 and, for the first time, the blaVIM-2, blaOXA-48, and blaIMP-13 genes were identified in Aeromonas spp. Among the 3GC-resistant isolates, the blaGES-5 and blaMOX genes were the most prevalent. Of the 10 isolates examined, three were capable of transferring carbapenem resistance to susceptible recipient E. coli. Our results suggest that conventionally treated municipal and untreated hospital wastewater is a reservoir for 3GC- and carbapenem-resistant, potentially harmful Aeromonas spp. that can be introduced into aquatic systems and pose a threat to both the environment and public health.